Symbolic Expression at the International Criminal Tribunal for the Former Yugoslavia - Aksenova, Marina (Oxford Academic, 2020)
The chapter argues that, at the creation of International Criminal Tribunal for the former Yugoslavia (ICTY), conditions were ripe for establishing this kind of forum. The ICTY was instituted with one overarching aim: condemnation of evil deemed universal. The language of the UN Security Council resolutions demonstrates an intensifying concern over offences committed in the Balkan war. The overarching purpose of the tribunal was symbolic—to uphold the value of human dignity through the ritual of criminal prosecutions in the light of the inability of local actors to prevent further escalation of atrocities. The chapter relies on two theoretical frameworks to support its claim: the theory of discourse analysis developed by Michel Foucault, projecting the ICTY’s power outwards focusing on the content of its input, and an anthropological exploration of the symbolic nature of rituals by Maurice Bloch, identifying the structure within which this content is generated.
Keywords: ICTY; Language; Symbolic purpose; Theory of discourse; Michel Foucault; Maurice Bloch; ODS 16 - Paz, justicia e instituciones sólidas